Intestinal malrotation - Arruti, César H (Cirugía del Uruguay, 1973)
Malrotation is reported as responsa ble of a high number of cases of duodeno-yeyunal obstruction. Analysis is made of obstructive mechanisms: a) volvulus of medium intestine, favourished by the precarious fixation of the mesentery; b) Ladd's band. Embriology of ombilical anse and its abnormal positions are remembered. Clinical feature are described, emphasazing vomiting as majar symptom as well as its characteristics: time of appearence, its containsts, evolution and consequences. Diagnostic is also considered, based on clinical features and Jaboratory tests, specially radiology. Treatment is studied, refering the most employed surgical .actics as wel! as pre and postoperative management. Results are considered with analysis of causes of death.